Ultrasound in Gynecology An Atlas and Guide - Sibal, Mala.; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2017)
This atlas and guide book is focused on gynecological ultrasound, an area that has remained in the shadow of obstetric ultrasound & fetal medicine. Gynecological ultrasound has seen rapid advances owing to expanding research and improved ultrasound equipment. This book leverages these advances and provides abundant illustrations and practice points of classical and new ultrasound features. It serves as a guide for radiologists, gynecologists and sonologists for the accurate diagnosis of gynecological pathologies. The chapters of this book also serve as a comprehensive resource for various topics with hundreds of images and figures, including basic gray scale images, Doppler studies and three dimensional ultrasound illustrations. In addition, standard terms for the evaluation and reporting of gynecological pathologies are discussed. Emergencies like ovarian torsion, complex adnexal cyst are also covered.
Introduction -- General Techniques in Gynecological Ultrasound -- Ultrasound Evaluation of Myometrium -- Ultrasound Evaluation of Endometrium -- Ultrasound Evaluation of Cervix -- Ultrasound Evaluation of Vagina -- Ultrasound Evaluation of Ovaries -- Endometriosis -- Ultrasound Evaluation of Adnexal Pathologies.-Ultrasound Evaluation of Pregnancy Related Pathologies -- Torsion -- Ultrasound Evaluation of Congenital Uterine Anomalies -- Ultrasound in other Miscellaneous Conditions -- Exploring Pathologies based on Clinical Presentation.
Keywords: Medicine; Gynecology; Radiology; Medicine & Public Health; Gynecology; Imaging / Radiology